Analysis of the Concept of al-Akhlak al-Karimah Based on the Thoughts of Sheikh Abd al-Wahhab al-Sya'rani and Sheikh Muhammad Abd al-Aziz al-Khawli - Baihaqi, Moh. Hamdan; Imron, Ali; Arifin, Bustanul (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2024)
Morals are the implementation of one's faith when meeting other people, other creatures or even meeting their Lord. So the discussion will not run out of time. Then in modern times, people begin to appear who heresy someone else just because they think that person does not practice morals in accordance with the guidance of the Prophet. The accusation is often leveled at the Sufis, especially the Sufis who often 'uzlah and do things outside the habits of other humans. Even though this is not true, the true Sufis are people who do worship both socially and individually in a way that is based on the Prophet Muhammad Saw and they will do it with sincerity. So we aim to combine the thoughts of a hadith expert with a Sufism expert to see how true the irregularities they throw at the Sufis are. This study uses a literature review method or literature study with analytical techniques comparing the opinions of two figures related to noble character. This study aims to find common ground between the opinions of Sheikh Abdul Wahhab al-Sya'rani and Sheikh Muhammad Abdul Aziz al-Khawli regarding morality.